Od orzeczenia o potrzebie kształcenia specjalnego do indywidualnego programu edukacyjno-terapeutycznego - WIELEBSKI, MARIUSZ (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Mariusz Wielebski, Od orzeczenia o potrzebie kształcenia specjalnego do indywidualnego programu edukacyjno-terapeutycznego [From the decision on special education eligibility to an individual educational and therapeutic plan]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 339-354. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.19 In my article I would like to show the complicated way from the decision about special education to individual educational and therapeutic plan. I am going to show how government statements are sometimes hard and complicated for parents, teachers and other specialists, who are looking after the children with special educational needs. I try to show everyday life in my job – teacher, specialist of pedagogical therapy. I hope my article will help and change our reality.